Students' Mathematical Understanding Ability Through the M-Apos Approach on Derivative Materials - Hanisa Tamalene; Anderson Leonardo Palinussa; R.H. Yanti Silitonga (STAI Hubbulwathan Duri, 2022)
This study aimed to improve students' mathematical understanding skills. The understanding ability is students' ability to understand the concept of the material, not just memorize the material. When students understand the concepts of differential calculus, students can quickly solve problems in differential calculus. The students' understanding gained in the differential calculus material will be the basis for understanding the integral and advanced calculus material. However, the current conditions where the Coronavirus that has hit the world, including Indonesia, have resulted in students having to study from home with a learning process that is carried out online. Students cannot access books in the library and limited credit to access teaching materials from the internet because the learning materials owned by students are limited. It makes it difficult for students to learn, so students' mathematical understanding abilities are low. The M-APOS learning approach was used in this study to answer this problem. The study results found that learning with this approach has succeeded in increasing students' mathematical understanding abilities on derivative material. This research is an experimental study with a pretest-posttest control group research design.